2012
DOI: 10.1093/bja/aes164
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide exposure does not seem to be associated with increased mortality, stroke, and myocardial infarction: a non-randomized subgroup analysis of the General Anaesthesia compared with Local Anaesthesia for carotid surgery (GALA) trial

Abstract: Given the greater prevalence of vascular risk factors in the nitrous oxide group and the lack of any definite effect on the primary outcome measure, these data do not support a clinically meaningful adverse effect of nitrous oxide on our composite outcome in patients undergoing carotid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
1
14
1
Order By: Relevance
“…Sanders et al found that the occurrence of cardiovascular events did not increase with N2O [20], results aligned with other authors' studies [17,19]. The PONV linked with N 2 O were investigated and it was found that there may be a time relation (longer expositions lead to higher incidence of PONV) [21].…”
Section: Nitrous Oxidesupporting
confidence: 56%
See 1 more Smart Citation
“…Sanders et al found that the occurrence of cardiovascular events did not increase with N2O [20], results aligned with other authors' studies [17,19]. The PONV linked with N 2 O were investigated and it was found that there may be a time relation (longer expositions lead to higher incidence of PONV) [21].…”
Section: Nitrous Oxidesupporting
confidence: 56%
“…In addition, no evidence exists that recommends, without any doubt, its discontinuation and, most importantly, health professionals are not at risk when N 2 O is used in modern, state of the art operating rooms with adequate scavenging systems [4,24]. Table 2 Decreases hyperalgesia of opioids [2,23] Inhibition of methionine synthetase [13] Decreases chronic postsurgical pain [23] Increase bowel volume and pressure in closed spaces [14] Good vehicle of volatiles (less dose) [24] Reduce protein synthesis promoting surgical site infection [15,16] Similar infection rate [13,19] Increased vascular risk in perioperative period [17] No increase in cardiovascular effects [20,19] Increase PONV [16] Small increase (resolved with one anti-emetic)…”
Section: Nitrous Oxidementioning
confidence: 99%
“…Nitrous oxide is known to increase plasma homocysteine concentration thereby impairing the endothelial function [15]. No association has been demonstrated in several large studies between intraoperative administration of nitrous oxide and postoperative stroke [15][16][17]. But due to the high risk involved in this case, it could have been totally avoided.…”
Section: Discussionmentioning
confidence: 98%
“…There are no known associations between anesthetic type and risk for stroke; however, future clinical trials are needed to confirm the apparent lack of association (86)(87)(88). Intraoperative use of metoprolol may increase stroke risk, and the authors of the Consensus Statement suggest using short-acting beta blockers such as esmolol instead.…”
Section: Perioperative Stroke: Anesthesiologist's Perspectivementioning
confidence: 99%
“…Several clinical trials have been conducted on these matters (87)(88)(89). Stroke outcomes do not appear to be correlated with general anesthesia versus local anesthesia for patients undergoing carotid endarterectomy, and there is no apparent increased risk of stroke with nitrous oxide exposure (87,88). Anesthetics can be neurotoxic if the local concentration becomes too high or if the patient is exposed for long durations; conversely, adequate anesthesia exposure may be neuroprotective (66).…”
Section: Perioperative Stroke: Anesthesiologist's Perspectivementioning
confidence: 99%